Battery diaphragm, preparation method thereof and lithium ion battery

By introducing heat-resistant ceramic coating, porous oily coating and spacer coating into the lithium-ion battery separator, the problem of the battery separator being prone to breaking the bridge and abnormal appearance after being wound, achieving higher circulation performance and product yield.

CN119812678AActive Publication Date: 2025-04-11HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411878229.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are prone to diffusion and breaking of electrolyte in the gap after being wound, causing lithium-ion evolution, and are prone to abnormal appearance such as streaks or explosive tendons during winding, which affects product yield.

Method used

A battery separator is employed, which includes a base film, a heat-resistant ceramic coating, a porous oily coating and a spacer coating layer. The heat-resistant ceramic coating improves the heat resistance of the membrane, the porous oil-based coating enhances the adhesion of the membrane to the electrode sheet and provides an electrolyte storage space. The space coating layer improves battery performance and reduces the risk of lithium evolution through the combination of oil-based coating units and blank units.

Benefits of technology

The battery separator improves the circulation performance of lithium-ion batteries, reduces the lithium-ion problem caused by insufficient adhesion, and reduces the risk of lithium-ion by optimizing the distribution of electrolyte, while improving the appearance quality of the battery and improving product yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812678A_ABST
    Figure CN119812678A_ABST
Patent Text Reader

Abstract

The invention discloses a battery diaphragm, a preparation method thereof and a lithium ion battery. The battery diaphragm comprises a base membrane, a heat-resistant ceramic coating, a porous oily coating and an interval coating, the heat-resistant ceramic coating is arranged on one surface of the base film; the porous oily coating is arranged on the surface, deviating from the base membrane, of the heat-resistant ceramic coating and comprises polymer particles and a first organic binder; the interval coating layer is arranged on the surface, deviating from the heat-resistant ceramic coating, of the base film and comprises a plurality of oily coating units which are arranged at intervals, blank units with the extending direction inclined to the length direction of the base film are formed between the adjacent oily coating units, and the oily coating units comprise inorganic filler and a second organic binder. By arranging the spaced coating layers and designing the extending direction of the blank unit in front of the adjacent oily coating units to be inclined to the length direction of the base membrane, the lithium separation risk of an interface can be reduced, the appearance abnormity such as streaks or bursting ribs in the rolling process of the diaphragm can be reduced, and the product yield can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a battery separator and a preparation method thereof, and a lithium ion battery. Background Art

[0002] With the increasing shortage of fossil fuels and the rise of the new energy industry, lithium-ion batteries have the advantages of high energy density, good rate performance, low self-discharge rate, no memory effect, and green environmental protection, and are widely used as energy storage, power and consumer products. Lithium-ion batteries are mainly composed of five main materials: positive electrode, negative electrode, diaphragm, electrolyte and battery packaging materials. Among them, the diaphragm is located between the positive electrode and the negative electrode. Its main function is to separate the positive and negative electrodes and prevent the two electrodes from contacting and causing a short circuit in the battery. At the same time, it also has the function of allowing electrolyte ions to pass through. Therefore, the performance of the diaphragm will directly affect the performance of the lithium-ion battery.

[0003] In order to improve the performance of the diaphragm, the mainstream solution in the market is to apply a modified coating on the surface of the diaphragm. There is an existing technology that sets a plurality of strip-shaped modified coatings on the diaphragm base layer, which are arranged at intervals along the width direction of the diaphragm base layer. A gap is formed between adjacent strip-shaped modified coatings along the length direction of the diaphragm base layer, and then a buffer space is formed between the positive and negative electrodes through the gap, so as to release the stress generated by the expansion of the positive and negative electrodes during the charge and discharge process. Extrusion of the corners. However, after the diaphragm is rolled into a battery cell, it is easy for the gap in the middle to break due to electrolyte diffusion, resulting in lithium deposition on the main interface; in addition, when the diaphragm is rolled up, it is easy to have appearance abnormalities such as winding streaks or burst ribs, which affects the product yield. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a battery separator and a preparation method thereof and a lithium ion battery.

[0005] In a first aspect of the present invention, a battery separator is provided, comprising:

[0006] Basement membrane;

[0007] A heat-resistant ceramic coating is disposed on a surface of the base film;

[0008] A porous oily coating is disposed on the surface of the heat-resistant ceramic coating away from the base film; the components of the porous oily coating include polymer particles and a first organic binder;

[0009] A spacing coating layer is arranged on the surface of the base film away from the heat-resistant ceramic coating; the spacing coating layer includes a plurality of oily coating units arranged at intervals, and blank units are formed between adjacent oily coating units, and the extension direction M of the blank units is inclined to the length direction P of the base film; the components of the oily coating unit include inorganic fillers and a second organic binder.

[0010] According to the battery separator of the embodiment of the present invention, at least the following beneficial effects are achieved: the battery separator can be used in lithium-ion batteries, and can further be used in wound lithium-ion batteries, wherein a heat-resistant ceramic coating is arranged on one surface of the base film, which can improve the heat resistance of the separator; a porous oily coating including polymer particles and a first organic binder is further arranged on the surface of the heat-resistant ceramic coating away from the base film, which can improve the adhesion between the separator and the pole piece, improve the cycle performance of the battery and prevent the problem of OH lithium precipitation caused by insufficient adhesion, and at the same time, its porous structure can provide electrolyte storage space to prevent the electrolyte from being completely squeezed out in the late cycle to cause corner lithium precipitation; in addition, the heat-resistant ceramic coating away from the base film The surface of the battery is provided with a spacing coating layer including a plurality of oily coating units arranged at intervals. On the one hand, each oily coating unit has a bonding function to ensure the bonding between the diaphragm and the electrode piece. On the other hand, the blank units between adjacent oily coating units can provide more electrolyte storage space, while reducing the ion transmission resistance and improving the battery performance. Moreover, the extension direction M of the blank units between adjacent oily coating units is inclined to the length direction P of the base film, which is conducive to promoting the electrolyte to diffuse from the head to the tail to the middle after the battery cell is wound, reducing the risk of lithium precipitation in the middle due to electrolyte bridge breakage, and at the same time reducing the appearance abnormalities such as streaks or rib bursts during the winding process of the diaphragm, thereby improving the product yield.

[0011] Among them, the extension direction M of the blank unit on the spacer coating layer is inclined to the length direction P of the base film, that is, the angle between the extension direction M of the blank unit and the length direction P of the base film is greater than 0° and less than 90°, and the blank unit and the base film are not perpendicular or parallel.

[0012] In some embodiments of the present invention, the angle between the extension direction M and the length direction P is 30° to 60°. Furthermore, the angle between the extension direction M of the blank unit and the length direction P of the base film can be controlled to be 42° to 48°. Among them, if the angle is controlled too large, the plate roller processing is more difficult and the cost is higher, and if the plate roller tends to be sheared vertically with the scraper during processing, it will cause serious wear of the plate roller; and if the angle is too small, after the battery separator is used to assemble the battery, the electrolyte is prone to broken bridge during transmission. Therefore, by controlling the angle between the extension direction M of the blank unit and the length direction P of the base film within the above range, it can be effectively ensured that the electrolyte can diffuse from the head to the middle as much as possible, so that lithium precipitation will not occur in the middle due to the broken bridge of the electrolyte, and it can effectively reduce or even avoid the appearance abnormalities such as streaks or ribs of the winding, improve the product yield, and at the same time, it is more convenient to process and can reduce the wear of the plate roller.

[0013] In some embodiments of the present invention, the adjacent oily coating unit and the blank unit satisfy: W1 / W2=0.5-3, wherein W1 is the width of the oily coating unit perpendicular to the extension direction M, and W2 is the width of the blank unit perpendicular to the extension direction M. Further, the adjacent oily coating unit and the blank unit can be controlled to satisfy: W1 / W2=1-2. If the width ratio of the oily coating unit to the blank unit is too small, the spacing coating layer has low overall adhesion to the pole piece, which will deteriorate the cycle interface.

[0014] The width W1 of each oily coating unit may be the same or different, or the width W1 of some of the oily coating units may be the same; the component configuration of each oily coating unit may be the same or different, or some of them may be the same. The width W2 of each blank unit may be the same or different, or some of them may be the same. In order to improve the uniformity of the structure, each oily coating unit may be evenly distributed on the surface of the base film.

[0015] According to research, the water-based coating formed by preparing the coating slurry with water as a diluent has poor adhesion, and the risk of OH lithium precipitation due to poor adhesion is prone to occur at the OH position of the battery cell (i.e., the position where the diaphragm exceeds the negative electrode sheet in the width direction and the position where the negative electrode sheet exceeds the positive electrode sheet in the width direction). Therefore, the battery diaphragm of the present invention is provided with a porous oily coating on the surface of the heat-resistant ceramic coating away from the base film, that is, the coating preparation process uses an organic solvent as a diluent to prepare the coating slurry, and the obtained porous oily coating has a high adhesiveness compared to the water-based coating, which can ensure that the overall interface of the coating to the electrode sheet is good, and reduce the risk of lithium precipitation due to poor adhesion at the interface OH position.

[0016] The components of the porous oily coating include polymer particles and a first organic binder; further, the mass ratio of the polymer particles to the first organic binder can be controlled at 1:1.5 to 2.5, for example, the mass ratio of the polymer particles to the first organic binder can be 1:2, 1:1.5 or 3:7.

[0017] In some embodiments of the present invention, in the porous oily coating, the particle size distribution width of the polymer particles satisfies: 0<(D90-D10) / D50≤3, preferably 1-3; and the difference (Tf-Tg) between the flow temperature Tf and the glass transition temperature Tg of the polymer particles is 10℃~50℃. Among them, for polymer particles, if (D90-D10) / D50 is too large, it means that its particle size distribution is too wide and the particle size is dispersed, which will cause large fluctuations in the coating thickness, have a great impact on the subsequent process of battery cell manufacturing, and easily cause the tabs to be misaligned when the battery cell is wound. If the Tf-Tg of the polymer particle size is too small, the polymer microsphere structure is easy to collapse, and it cannot play a supporting role and cannot effectively improve the corner. The above large-particle polymer particles are combined with the first organic binder to construct a porous oily coating, wherein the polymer particles have certain compressibility and support properties, can provide more space for electrolyte storage, can alleviate the problem of lithium deposition in corners caused by electrolyte being squeezed out due to electrode expansion, and can reduce the risk of breakage due to excessive internal stress caused by electrode expansion.

[0018] Furthermore, the particle size distribution width of the polymer particles used can be controlled to satisfy (D90-D10) / D50=2-2.5, and the polymer particles can satisfy Tf-Tg of 20°C-50°C.

[0019] In addition, when the polymer particles satisfy (D90-D10) / D50=1-3, the D50 particle size of the polymer particles can be controlled to be 5um-15um; further, when the polymer particles satisfy (D90-D10) / D50=2-2.5, the D50 particle size of the polymer particles can be controlled to be 7um-10um. Among them, D50 cannot be too large or too small. If D50 is too large, the overall thickness of the porous oily coating is large, and the electrolyte is prone to breakage at the corners of the battery cell after compression, resulting in lithium deposition; if it is too small, the overall compressible space of the coating is small, and it cannot effectively improve the lithium deposition.

[0020] In some embodiments of the invention, the molecular weight of the first organic binder is 30W to 100W, and the first organic binder has a characteristic peak when the diffraction angle 2θ is between 10° and 40°. The first organic binder has a characteristic peak when the diffraction angle 2θ is between 10° and 40°, and has good crystallinity, with a crystallinity of approximately 15% to 35%, which can ensure small swelling in the electrolyte. The molecular weight of the organic binder is between 30W and 100W, and its Young's modulus is between 500MPa and 2000MPa. It has good adhesion to the pole piece and can ensure a good circulation interface.

[0021] Further, the molecular weight of the first organic binder may be 60W to 80W, and its Young's modulus is between 600MPa and 1500MPa; or the molecular weight of the first organic binder is 30W to 80W, 30W to 70W, 45W to 75W, or 50W to 70W. The first organic binder has a characteristic peak when the diffraction angle 2θ is between 15° and 30°, or has a characteristic peak when the diffraction angle 2θ is between 20° and 25°.

[0022] In some embodiments of the present invention, the polymer particles are selected from at least one of polyamide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, and acrylate copolymers;

[0023] And / or, the first organic binder is selected from at least one of polyvinylidene fluoride, polyethylene difluoride, polytetrafluoroethylene, hexafluoropropylene, and trifluoroethylene.

[0024] In some embodiments of the present invention, the thickness of the porous oily coating is 0.5 μm to 5 μm. Further, the thickness of the porous oily coating may be 0.5 μm to 3 μm, 1 μm to 4 μm, 1 μm to 2 μm, 1.5 μm to 3 μm, 2 μm to 4 μm or 3 μm to 5 μm.

[0025] In some embodiments of the present invention, the components of the heat-resistant ceramic coating include an inorganic ceramic material and a heat-resistant glue; the particle size distribution width of the inorganic ceramic material satisfies: (D90-D10) / D50=0.5~2, and the glass transition temperature of the heat-resistant glue is greater than or equal to 180°C. Among them, for inorganic ceramic materials, if (D90-D10) / D50 is too large, it means that the particle size distribution width of the material is too wide, and there are too many large and small particle size powders, which will make the coating not compact enough, the effect of thermal shock resistance will be worse, and the porosity of the coating will be reduced, and the lithium ion transmission resistance will increase; for heat-resistant glue, if its glass transition temperature is too small, the heat resistance of the coating is poor.

[0026] Further, the components of the heat-resistant ceramic coating may include 95 wt % to 98 wt % of inorganic ceramic material and 2 wt % to 5 wt % of heat-resistant glue.

[0027] Furthermore, the particle size distribution width of the inorganic ceramic material can be controlled to satisfy: (D90-D10) / D50=1-1.5, and the glass transition temperature of the heat-resistant glue is greater than or equal to 200°C.

[0028] Furthermore, when the inorganic ceramic material satisfies (D90-D10) / D50=0.5~2, the D50 particle size can be controlled to be 100nm~500nm; when the inorganic ceramic material satisfies (D90-D10) / D50=1~1.5, the D50 particle size can be controlled to be 200nm~400nm.

[0029] Furthermore, the specific surface area of ​​the inorganic ceramic material can be controlled to be 10m 2 / g~50m 2 / g.

[0030] In some embodiments of the present invention, the inorganic ceramic material is selected from at least one of silica, alumina, silicon oxide, calcium oxide, magnesium oxide, ZnO, TiO2, boehmite, and ceramic fiber; and / or the heat-resistant glue is selected from at least one of polyacrylic acid and styrene-butadiene rubber.

[0031] In some embodiments of the present invention, the heat-resistant ceramic coating is a water-based heat-resistant ceramic coating, and the coating preparation process uses water as a diluent to prepare the coating slurry.

[0032] In some embodiments of the present invention, the thickness of the heat-resistant ceramic coating is 0.5 μm to 3 μm. Further, the thickness of the heat-resistant ceramic can be controlled to be 0.5 μm to 1 μm, 1 μm to 2.5 μm, 1 μm to 2 μm, 1.5 μm to 3 μm, 1.5 μm to 2.5 μm or 2 μm to 3 μm.

[0033] A spacer coating layer is set on the surface of the base film away from the heat-resistant ceramic coating. The spacer coating layer is constructed by an oily coating unit. An organic solvent is used as a diluent in the coating slurry preparation process. The obtained spacer coating layer is an oily coating. Compared with the water-based coating, the adhesion can also be improved, thereby ensuring a good overall interface between the coating and the electrode and reducing the risk of lithium plating.

[0034] The interval coating layer includes a plurality of oily coating units arranged at intervals, and the oily coating unit is constructed of components including an inorganic filler and a second organic binder, specifically a porous oily coating unit. Since the adhesion of the water-based coating is relatively low, each coating usually needs to be coated and set separately during the preparation process, which is costly. In the present invention, both the porous oily coating and the interval coating layer are porous oily layer bodies, and the coating and setting of both sides can be performed at one time during the preparation, thereby reducing the cost. Furthermore, the components of the oily coating unit may include 5wt% to 15wt% of the inorganic filler and 85wt% to 95wt% of the second organic binder.

[0035] In some embodiments of the present invention, in the spacer coating layer, the molecular weight of the second organic binder is 30W to 100W, and the second organic binder has a characteristic peak at a diffraction angle 2θ between 10° and 40°. The above second organic binder has good crystallinity and adhesion, can reduce the sol in the electrolyte, and ensure a good circulation interface between the coating and the pole piece.

[0036] In some embodiments of the present invention, in the spacer coating layer, the particle size distribution width of the inorganic filler satisfies: (D90-D10) / D50=1-3. The D50 particle size of the inorganic filler can be controlled to be 500nm-1000nm. By controlling the particle size distribution width of the inorganic filler within the above range, the particle size is relatively uniform, which can improve the uniformity of the coating structure.

[0037] In some embodiments of the present invention, the inorganic filler is selected from at least one of silica, alumina, silicon oxide, calcium oxide, magnesium oxide, ZnO, TiO2, boehmite, and ceramic fiber;

[0038] And / or, the second organic binder is selected from at least one of polyvinylidene fluoride, polyethylene difluoride, polytetrafluoroethylene, hexafluoropropylene, and trifluoroethylene.

[0039] In some embodiments of the present invention, the thickness of the spacer coating layer is 0.5 μm to 1.5 μm. Further, the thickness of the spacer coating layer can be controlled to be 0.5 μm to 1 μm, 0.8 μm to 1.6 μm or 1 μm to 1.5 μm.

[0040] In some embodiments of the present invention, the base film is selected from one or more composite films of PE film, PP film, PET film, and PI film.

[0041] In some embodiments of the present invention, the base film has a thickness of 1 μm to 20 μm. Further, the base film may have a thickness of 3.0 μm to 15.0 μm, 5 μm to 12 μm, 6 μm to 10 μm, 4 μm to 8 μm, or 5 μm to 17 μm.

[0042] In some embodiments of the present invention, the surface density of the base film can be controlled at 1.0 g / m 2 ~12.0g / m 2 ; The porosity of the basement membrane can be controlled to be greater than or equal to 30%; The tortuosity of the basement membrane can be controlled to be less than or equal to 5.

[0043] In a second aspect of the present invention, a method for preparing any of the above-mentioned battery separators is provided, comprising the following steps:

[0044] Disposing a heat-resistant ceramic coating on one surface of the base film;

[0045] A first oily slurry is prepared by mixing a component including polymer particles and a first organic binder with a first organic solvent, and a second oily slurry is prepared by mixing a component including an inorganic filler and a second organic binder with a second organic solvent;

[0046] The first oily slurry is coated on the surface of the base film away from the heat-resistant ceramic layer; at the same time, the second oily slurry is coated at intervals on the surface of the base film away from the heat-resistant ceramic coating, and the extension direction of the blank area between adjacent coating areas is inclined to the length direction of the base film, and a battery separator is obtained after drying.

[0047] In the above preparation method, the first oily slurry and the second oily slurry are coated on both sides of the composite film material composed of the base film and the heat-resistant ceramic coating at one time, which can simplify the preparation process and reduce production costs. The structural setting of the corresponding battery separator has the corresponding beneficial effects of the above-mentioned battery separator.

[0048] In some embodiments of the present invention, providing a heat-resistant ceramic coating on a surface of a base film comprises: preparing a heat-resistant ceramic slurry by mixing components including an inorganic ceramic material and a heat-resistant glue with solvent water, and then coating the heat-resistant ceramic slurry on a surface of the base film using a micro-gravure roller, and forming a heat-resistant ceramic layer after drying.

[0049] In some embodiments of the present invention, the components of the heat-resistant ceramic slurry further include an auxiliary agent, and the auxiliary agent includes at least one of a dispersant and a wetting agent. For example, the auxiliary agent may be one or more of phosphate esters, acetylenic diols, polycarboxylic acid polymers, polysiloxanes, arylphenyl polyethoxyalkylene ethers, polyethers, and the like.

[0050] In some embodiments of the present invention, the first oily slurry may be coated on the surface of the base film away from the heat-resistant ceramic layer using a micro-gravure roller.

[0051] In some embodiments of the present invention, the coating of the second oily slurry can be specifically applied by using a gap anilox roller to coat the second oily slurry at intervals on the surface of the base film away from the wear-resistant ceramic coating; wherein the gap anilox roller has coating areas arranged at intervals and used for coating the slurry, and there are recessed blank areas between adjacent coating areas, and the extension direction of the recessed blank areas is 30° to 60° with respect to the rotation direction of the gap anilox roller. Furthermore, the ratio of the width of the coating area on the gap anilox roller along the extension direction perpendicular to the recessed blank areas to the width of the recessed blank areas along the extension direction perpendicular to the extension direction thereof is 0.5 to 3.0.

[0052] In a third aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, and a separator sandwiched between the positive electrode sheet and the negative electrode sheet, wherein the separator is any one of the aforementioned battery separators.

[0053] In some embodiments of the present invention, the porous oily coating on the battery separator is disposed toward the positive electrode sheet, and the spacer coating layer is disposed toward the negative electrode sheet.

[0054] In some embodiments of the present invention, the porous oily coating on the battery separator is disposed toward the negative electrode sheet, and the spacer coating layer is disposed toward the positive electrode sheet.

[0055] In some embodiments of the present invention, the lithium ion battery is a wound lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0057] Figure 1 This is a schematic diagram of the structure of the battery separator of Example 1;

[0058] Figure 2 Schematic diagram of the surface structure of the spacer coating layer in the battery separator of Example 1. DETAILED DESCRIPTION

[0059] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0060] Example 1

[0061] This embodiment provides a battery separator, the structure of which is as follows: Figure 1 As shown, it includes a base film 11, a heat-resistant ceramic coating 12, a porous oily coating 13 and a spacer coating layer 14.

[0062] The heat-resistant ceramic coating 12 is disposed on one surface of the base film 11. In this embodiment, the base film 11 is a PE film, and the heat-resistant ceramic coating 12 is a water-based coating; in terms of mass percentage, its components include 94% of inorganic ceramic material, 5% of heat-resistant glue, and 1% of auxiliary agent acetylene glycol; the inorganic ceramic material specifically uses boehmite with a particle size distribution width (D90-D10) / D50 of 1.33 and D50 of 0.3 μm, and the heat-resistant glue uses modified styrene-butadiene rubber (manufacturer: Kraton, USA, product model: MD6951) with a glass transition temperature of 210°C.

[0063] The porous oily coating 13 is disposed on the surface of the heat-resistant ceramic coating 12 away from the base film 11, and the components of the porous oily coating 13 include polymer particles and a first organic binder. In this embodiment, the polymer particles are acrylic copolymer particles (manufacturer: Shenzhen Delixin Material Technology Co., Ltd., product model: CFL) with a particle size distribution width (D90-D10) / D50 of 1.5, D50 of 5um, and a difference (Tf-Tg) between the flow temperature Tf and the glass transition temperature Tg of 25°C; the first organic binder is polyvinylidene fluoride (manufacturer: East Sunshine Group, product model: 601A) with a molecular weight of 70W and a characteristic peak at a diffraction angle 2θ between 20° and 25°, wherein the mass ratio of the polymer particles to the first organic binder is 3:7.

[0064] The spacer coating layer 14 is disposed on the surface of the base film 11 away from the heat-resistant ceramic coating 12. The spacer coating layer 14 includes a plurality of oily coating units 141 disposed at intervals. A blank unit 142 is formed between adjacent oily coating units 141. The extension direction M of the blank unit 142 is inclined to the length direction P of the base film 11. Figure 2 As shown; the components of the oily coating unit 141 include an inorganic filler and a second organic binder. In this embodiment, the inorganic filler uses alumina (manufacturer: Zhejiang Jidun New Materials Technology Co., Ltd., product model: AP55) with a particle size distribution width satisfying: (D90-D10) / D50=1~3, specifically, D10=0.2um, D50=0.5um, D90=1.2um; the second organic binder uses polyvinylidene fluoride (manufacturer: East Sunshine Group, product model: 601A) with a molecular weight of 70W and a characteristic peak at a diffraction angle 2θ between 20° and 25°; in terms of mass percentage, the components of the oily coating unit 141 include 20% of the inorganic filler and 80% of the second binder. In this embodiment, the angle between the extension direction M of the blank unit 142 and the length direction P of the base film 11 is 45°, the oily coating unit 141 is evenly distributed on the surface of the base film 11, and the adjacent oily coating units 141 and the blank units 142 satisfy: W1 / W2=1.5, wherein W1 is the width of the oily coating unit 141 along the extension direction M perpendicular to the blank unit 142, and W2 is the width of the blank unit 142 along the extension direction M perpendicular to the blank unit 142.

[0065] The preparation method of the battery separator comprises the following steps:

[0066] S1. According to mass percentage, 94% of inorganic ceramic material boehmite with a particle size distribution width (D90-D10) / D50 of 1.33 and D50 of 0.3 μm, 5% of heat-resistant rubber styrene-butadiene rubber with a glass transition temperature of 210°C and 1% of auxiliary agent acetylene glycol are taken, and they are uniformly dispersed in deionized water, and mixed and stirred to obtain heat-resistant ceramic slurry;

[0067] S2, coating a layer of heat-resistant ceramic slurry on one surface of the PE base film using a 180LPI micro-gravure roller, and obtaining a heat-resistant ceramic coating with a thickness of 1 μm after drying;

[0068] S3, dispersing large-diameter polymer acrylate copolymer particles with a particle size distribution width (D90-D10) / D50 of 1.5, D50 of 5 um, and a difference between the flow temperature Tf and the glass transition temperature Tg of 25°C in an organic solvent N-methylpyrrolidone to prepare a dispersion with a solid content of 10%; dissolving a first organic binder polyvinylidene fluoride with a molecular weight of 70W and a characteristic peak before the diffraction angle 2θ is 20° to 25° in an organic solvent N-methylpyrrolidone to obtain a binder solution with a solid content of 10%; then mixing the dispersion and the binder solution at a mass ratio of acrylate copolymer particles to polyvinylidene fluoride of 3:7 to obtain a first oily slurry;

[0069] S4. Take 80% of the second organic binder polyvinylidene fluoride with a molecular weight of 70W and a characteristic peak before the diffraction angle 2θ is 20° to 25° and 20% of the inorganic filler alumina according to mass percentage, dissolve the polyvinylidene fluoride in N-methylpyrrolidone, and disperse the alumina in N-methylpyrrolidone, mix and stir evenly to obtain a second oily slurry.

[0070] S5, using a conventional 180LPI micro-gravure roller to apply the first oily slurry prepared in step S3 to the surface of the heat-resistant ceramic coating prepared in step S2 that is away from the PE base film; and simultaneously using a 180LPI gap anilox roller to apply the second oily slurry prepared in step S4 to the surface of the PE base film that is away from the heat-resistant ceramic coating, wherein the coating of the first oily slurry and the second oily slurry is completed at one time; the 180LPI gap anilox roller has coating areas that are spaced apart and used for coating the slurry, and adjacent coating areas are spaced apart from each other. There are recessed blank areas between the material areas, the extension direction of the recessed blank areas is 45° to the rotation direction of the gap anilox roller, and the ratio of the width W1' of the coating area along the extension direction perpendicular to the recessed blank areas to the width W2' of the recessed blank areas along the extension direction perpendicular to the same is W1' / W2'=1.5. After drying, a porous oily coating with a thickness of 4 μm is formed on the surface of the heat-resistant ceramic layer, and a spacing coating layer with a thickness of 1 μm is formed on the surface of the PE base film away from the heat-resistant ceramic layer to obtain a battery separator product.

[0071] Example 2

[0072] This embodiment proposes a battery separator, which differs from the battery separator of Example 1 in that the inorganic ceramic material component of the heat-resistant ceramic coating in the battery separator of this embodiment adopts boehmite (manufacturer: Zhejiang Jidun New Materials Technology Co., Ltd., product model: BP10) with a particle size distribution width (D90-D10) / D50 of 2.0 and D50 of 0.3μm instead of the boehmite in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0073] Example 3

[0074] This embodiment proposes a battery separator, which differs from the battery separator of Example 1 in that the component inorganic ceramic material of the heat-resistant ceramic coating in the battery separator of this embodiment adopts boehmite with a particle size distribution width (D90-D10) / D50 of 0.67 and D50 of 0.3μm (manufacturer: Zhejiang Jidun New Materials Technology Co., Ltd., the particle size distribution of the product is adjusted by screening based on the commercial product BP10) instead of the boehmite in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0075] Example 4

[0076] This embodiment proposes a battery separator, which differs from the battery separator of Example 1 in that the heat-resistant glue component of the heat-resistant ceramic coating in the battery separator of this embodiment adopts PAA (manufacturer Gao Rui) with a glass transition temperature Tg of 180°C instead of the styrene-butadiene rubber in Example 1, and the formulation, structure and preparation method of other components are the same as those in Example 1.

[0077] Example 5

[0078] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the component polymer particles of the porous oily coating in the battery separator of this embodiment use acrylate copolymer particles with a particle size distribution width (D90-D10) / D50 of 3, D50 of 5um, and Tf-Tg of 25°C (manufacturer: Shenzhen Delixin Material Technology Co., Ltd., model: CFL, product before spray drying and grading) to replace the acrylate copolymer particles in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0079] Example 6

[0080] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the component polymer particles of the porous oily coating in the battery separator of this embodiment use acrylate copolymer particles with a particle size distribution width (D90-D10) / D50 of 1.04, D50 of 4.8um, and Tf-Tg of 25°C (manufacturer: Shenzhen Delixin Material Technology Co., Ltd., model: CFL, product after spray drying and grading) to replace the acrylate copolymer particles in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0081] Example 7

[0082] This embodiment proposes a battery separator, which differs from the battery separator of Example 1 in that: the component polymer particles of the porous oily coating in the battery separator of this embodiment use acrylate copolymer particles with a particle size distribution width (D90-D10) / D50 of 1.5, D50 of 5um, and Tf-Tg of 10°C (manufacturer: Shenzhen Delixin Material Technology Co., Ltd., trade name: CFL) instead of the acrylate copolymer particles in Example 1, and the formulation, structure and preparation method of other components are the same as those in Example 1.

[0083] Example 8

[0084] This embodiment proposes a battery separator, which differs from the battery separator of Example 1 in that the first organic binder component of the porous oily coating in the battery separator of this embodiment adopts polyvinylidene fluoride (PVDF) with a molecular weight of 30W and a characteristic peak at a diffraction angle 2θ between 30° and 40° (manufacturer: Sinochem Blue Sky Group Co., Ltd.) instead of the polyvinylidene fluoride in Example 1, and the formulation, structure and preparation method of other components are the same as those in Example 1.

[0085] Example 9

[0086] This embodiment proposes a battery separator, which differs from the battery separator of Example 1 in that the first organic binder component of the porous oily coating in the battery separator of this embodiment adopts polyvinylidene fluoride (PVDF) with a molecular weight of 80W and a characteristic peak at a diffraction angle 2θ between 10° and 15° (manufacturer: Sinochem Blue Sky Group Co., Ltd., product model: 2703) instead of the polyvinylidene fluoride in Example 1, and the formulation, structure and preparation method of other components are the same as those in Example 1.

[0087] Example 10

[0088] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the width ratio of the adjacent oily coating unit and the blank unit on the spacing coating layer in this embodiment is W1 / W2=0.5, which is different from W1 / W2=1.5 in Example 1; the other structures are the same as those in Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the width ratio of the coating area and the recessed blank area on the gap anilox roller used in the preparation of the spacing coating layer is W1' / W2'=0.5, which is different from W1' / W2'=1.5 in Example 1, and the other preparation operations are the same as those in Example 1.

[0089] Embodiment 11

[0090] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the width ratio of the adjacent oily coating unit and the blank unit on the spacing coating layer in this embodiment is W1 / W2=3, which is different from W1 / W2=1.5 in Example 1; the other structures are the same as those in Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the width ratio of the coating area and the recessed blank area on the gap anilox roller used in the preparation of the spacing coating layer is W1' / W2'=3, which is different from W1' / W2'=1.5 in Example 1, and the other preparation operations are the same as those in Example 1.

[0091] Example 12

[0092] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the angle between the extension direction M of the blank unit on the spacing coating layer and the length direction P of the base film in this embodiment is 30°, which is different from 45° in Example 1; the other structures are the same as Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the extension direction of the concave blank area on the gap anilox roller used in the preparation of the spacing coating layer is 30° to the rotation direction of the gap anilox roller, which is different from 45° in Example 1; the other preparation operations are the same as Example 1.

[0093] Embodiment 13

[0094] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the angle between the extension direction M of the blank unit on the spacing coating layer and the length direction P of the base film in this embodiment is 60°, which is different from 45° in Example 1; the other structures are the same as Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the extension direction of the concave blank area on the gap anilox roller used in the preparation of the spacing coating layer is 60° to the rotation direction of the gap anilox roller, which is different from 45° in Example 1; the other preparation operations are the same as Example 1.

[0095] Embodiment 14

[0096] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the width ratio of the adjacent oily coating unit and the blank unit on the spacing coating layer in this embodiment is W1 / W2=1, which is different from W1 / W2=1.5 in Example 1; the other structures are the same as those in Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the width ratio of the coating area and the recessed blank area on the gap anilox roller used in the preparation of the spacing coating layer is W1' / W2'=1, which is different from W1' / W2'=1.5 in Example 1, and the other preparation operations are the same as those in Example 1.

[0097] Embodiment 15

[0098] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the width ratio of the adjacent oily coating unit and the blank unit on the spacing coating layer in this embodiment is W1 / W2=2, which is different from W1 / W2=1.5 in Example 1; the other structures are the same as those in Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the width ratio of the coating area and the recessed blank area on the gap anilox roller used in the preparation of the spacing coating layer is W1' / W2'=2, which is different from W1' / W2'=1.5 in Example 1, and the other preparation operations are the same as those in Example 1.

[0099] Example 16

[0100] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that the angle between the extension direction M of the blank unit on the spacing coating layer and the length direction P of the base film in this embodiment is 42°, which is different from 45° in Example 1; the other structures are the same as Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the extension direction of the concave blank area on the gap anilox roller used in the preparation of the spacing coating layer is 42° to the rotation direction of the gap anilox roller, which is different from 45° in Example 1; the other preparation operations are the same as Example 1.

[0101] Embodiment 17

[0102] This embodiment proposes a battery separator, which is different from the battery separator of Example 1 in that: the angle between the extension direction M of the blank unit on the spacing coating layer and the length direction P of the base film in this embodiment is 48°, which is different from 45° in Example 1; the other structures are the same as Example 1. Accordingly, in the preparation process of the battery separator of this embodiment, the extension direction of the concave blank area on the gap anilox roller used in the preparation of the spacing coating layer is 48° to the rotation direction of the gap anilox roller, which is different from 45° in Example 1; the other preparation operations are the same as Example 1.

[0103] Comparative Example 1

[0104] This comparative example proposes a battery separator, which is different from the battery separator of Example 1 in that: this comparative example 1 adjusts the porous oily coating in Example 1 to a porous water-based coating; the other structures are the same as those of Example 1. Accordingly, in the preparation process of the battery separator of this comparative example, an equal amount of water is used in step S3 to replace the organic solvent N-methylpyrrolidone used in step S3 of Example 1 to prepare an aqueous slurry, and in step S5, an aqueous slurry is used to replace the first oily slurry in Example 1 to prepare a porous water-based coating on the surface of the heat-resistant ceramic coating away from the PE base film. Due to the weak adhesion of the aqueous slurry, the coating setting of the porous water-based coating and the coating setting of the interval coating layer cannot be carried out at the same time, but are separately coated and prepared in sequence. Specifically, the aqueous slurry is first coated on the surface of the heat-resistant ceramic coating away from the PE base film, and the porous water-based coating is obtained after drying, and then the second oily slurry is coated on the surface of the PE base film away from the heat-resistant ceramic coating, and the interval coating layer is obtained after drying, and then the preparation of each layer on the base film is carried out through three coatings. The other components and preparation operations are the same as those in Example 1.

[0105] Comparative Example 2

[0106] This comparative example proposes a battery separator, which is different from the battery separator of Example 1 in that: in this comparative example, the angle between the extension direction M of the blank unit on the spacing coating layer and the length direction P of the base film is 0°, which is different from 45° in Example 1; the other structures are the same as the example. Accordingly, in the preparation process of the battery separator of this comparative example, the extension direction of the concave blank area on the gap anilox roller used in the preparation of the spacing coating layer is 0° to the rotation direction of the gap anilox roller, which is different from 45° in Example 1; the other preparation operations are the same as Example 1.

[0107] Comparative Example 3

[0108] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the angle between the extension direction M of the blank unit on the spacing coating layer and the length direction P of the base film in this comparative example is 90°, which is different from 45° in Example 1; the other structures are the same as those in the example. Accordingly, in the preparation process of the battery separator of this comparative example, the extension direction of the concave blank area on the gap anilox roller used in the preparation of the spacing coating layer is 90° to the rotation direction of the gap anilox roller, which is different from 45° in Example 1; the other preparation operations are the same as those in Example 1.

[0109] Comparative Example 4

[0110] This comparative example proposes a battery separator, which is different from the battery separator of Example 1 in that: a fully coated oily coating layer is used in this comparative example to replace the interval coating layer in Example 1, and the composition formulation and thickness of the oily coating layer in this comparative example are the same as those of the oily coating unit of the interval coating layer in Example 1, and the other structures are the same as those of Example 1. Accordingly, in the preparation process of the battery separator of this comparative example, the interval coating layer is prepared by using a 180LPI micro-gravure roller instead of the 180LPI gap anilox roller in Example 1, and the oily coating layer is prepared on the surface of the PE base film away from the heat-resistant ceramic layer; the other preparation operations are the same as those of Example 1.

[0111] Comparative Example 5

[0112] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the first organic binder component of the porous oily coating in the battery separator of this comparative example adopts polyvinylidene fluoride (PVDF) with a molecular weight of 20W and a characteristic peak at a diffraction angle 2θ between 0° and 10° (manufacturer: Sinochem Blue Sky Group Co., Ltd.) instead of the polyvinylidene fluoride in Example 1, and the formulation, structure and preparation method of other components are the same as those in Example 1.

[0113] Comparative Example 6

[0114] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the component polymer particles of the porous oily coating in the battery separator of this comparative example adopt acrylate copolymer particles (manufacturer: Shenzhen Delixin Material Technology Co., Ltd.) with a particle size distribution width (D90-D10) / D50 of 3.27, D50 of 5.5um, and Tf-Tg of 25°C to replace the acrylate copolymer particles in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0115] Comparative Example 7

[0116] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the component polymer particles of the porous oily coating in the battery separator of this comparative example adopt acrylate copolymer particles (manufacturer: Shenzhen Delixin Material Technology Co., Ltd.) with a particle size distribution width (D90-D10) / D50 of 0.83, D50 of 6um, and Tf-Tg of 25°C to replace the acrylate copolymer particles in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0117] Comparative Example 8

[0118] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the component polymer particles of the porous oily coating in the battery separator of this comparative example adopt acrylate copolymer particles (manufacturer: Shenzhen Delixin Material Technology Co., Ltd.) with a particle size distribution width (D90-D10) / D50 of 1.5, D50 of 5um, and Tf-Tg of 5°C to replace the acrylate copolymer particles in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0119] Comparative Example 9

[0120] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the heat-resistant glue component of the heat-resistant ceramic coating in the battery separator of this comparative example adopts PAA (manufacturer: Gao Rui) with a glass transition temperature Tg of 150°C instead of the styrene-butadiene rubber in Example 1, and the formulation, structure and preparation method of other components are the same as those in Example 1.

[0121] Comparative Example 10

[0122] This comparative example proposes a battery separator, which differs from the battery separator of Example 1 in that the inorganic ceramic material component of the heat-resistant ceramic coating in the battery separator of this comparative example adopts boehmite with a particle size distribution width (D90-D10) / D50 of 3.0 and D50 of 0.3μm to replace the boehmite in Example 1, and the formulation, structure and preparation method of other components are basically the same as those in Example 1.

[0123] The selection of some layer components and structural settings of the battery separators of the above embodiments and comparative examples are specifically shown in Table 1. The total coating thickness on each battery separator and the number of coating times in the coating preparation process on the base film are shown in Table 2. Among them, the total coating thickness is directly measured by a Mahr thickness gauge. The total coating thickness is obtained by coating the coating on the basis of the designed thickness, so the actual coating test thickness will fluctuate, so there will be differences; and the porous oil-based coating contains large-size polymer particles, which are not uniform spherical particles, and the width of their particle size distribution will also affect the total coating thickness, so the total coating thickness is different.

[0124] The battery separators of the above embodiments and comparative examples can be further applied to the preparation of lithium-ion batteries, and the specific preparation method includes:

[0125] S1. Preparation of positive electrode sheet: Mix the positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride in a mass ratio of 97:1.5:1.5, add N-methylpyrrolidone (NMP), and stir evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 8μm, and the aluminum foil is dried at 125°C for 1h to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, dry under vacuum conditions at 125°C for 2h to obtain a positive electrode with a specification of 65mm×860mm.

[0126] S2. Preparation of negative electrode sheet: Mix the negative electrode active material graphite, the binder styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 98:1:1, add deionized water, and stir evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 60wt%. The negative electrode slurry is evenly coated on one surface of a copper foil with a thickness of 6μm, and the copper foil is dried at 120°C to obtain a negative electrode coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode coated with a negative electrode material layer on both sides. Then, after cold pressing, cutting and slitting, dry under vacuum conditions at 120°C for 2h to obtain a negative electrode with a specification of 69mm×868mm.

[0127] S3. Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethyl oxalate (EC), propylene carbonate (PC) and dicarboxylic acid imide (DMC) are mixed in a mass ratio of 3:2:4 to obtain an organic solvent, and then lithium hexafluorophosphate is added to the organic solvent to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.

[0128] S4, assembly of lithium-ion battery: stack the positive electrode, separator, and negative electrode prepared above in order, place the separator between the positive electrode and the negative electrode to play a role of isolation, and wind to obtain an electrode assembly. Place the electrode assembly in an aluminum-plastic film packaging bag, inject electrolyte after drying, and obtain a lithium-ion battery through vacuum packaging, standing, formation, degassing, trimming and other processes.

[0129] The battery separators of Examples 1 to 17 and Comparative Examples 1 to 10 were further assembled into lithium-ion batteries using the above method, and the battery performance was further tested. The specific test items and test methods are as follows:

[0130] 1. Adhesion between battery separator and electrode (including positive electrode and negative electrode)

[0131] The test method is: after hot pressing the diaphragm and the corresponding pole piece at 93°C and 3Mpa for 5 minutes, test the force required for the two to be peeled off.

[0132] 2. Thermal shrinkage test of battery separator: Cut the separator into 30*70mm, bake it in an oven at 130℃ for 0.5h, take it out and cool it to room temperature, test the size A*Bmm after baking, and calculate the corresponding shrinkage. MD and TD represent the longitudinal and transverse shrinkage respectively.

[0133] 3. Gap value test: The Gap value is the difference in thickness of the battery separator before and after hot pressing. The test method is: first measure the thickness D1 of 8 layers of battery separator, then measure the thickness D2 of 8 layers of battery separator after hot pressing at 85℃ and 1Mpa for 1h. The Gap value is equal to D1-D2.

[0134] 4. Thickness after hot pressing: The thickness after hot pressing refers to the thickness of the coating after hot pressing. This thickness is a calculated value, which is equal to the total thickness minus the thickness change of the coating after hot pressing. The Gap value is the thickness of 8 layers, so the thickness of a single layer needs to be divided by 8, and then the thickness after hot pressing = total coating thickness - Gap value / 8.

[0135] 5. Cycle interface test: Place the lithium-ion battery in a 25°C environment, let it stand for 30 minutes, charge it to 4.50V at a constant current of 3.5C, then charge it to 0.05C at a constant voltage of 4.50V, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.7C. This is a cycle (cls). After 300cls, disassemble the battery interface and observe the lithium precipitation of the negative electrode sheet. Among them, OH represents the specific position of the battery lithium. In the battery, the diaphragm width> the negative electrode sheet width> the positive electrode sheet width. The position that exceeds the width is the OH position; lithium precipitation is generally on the negative electrode sheet, because the negative electrode potential is low and may reach below 0V, which is easy to cause lithium precipitation. Then the main lithium precipitation refers to the lithium precipitation on the battery plane, that is, the lithium precipitation on the entire surface of the negative electrode sheet. The standard for judging the degree of lithium precipitation is: the appearance of silvery white lithium single substance is judged as severe; only purple spots or black spots are judged by size, and if it is less than 1 / 10 of the battery height, it is mild, otherwise it is severe.

[0136] 6. High temperature external short circuit test: Place the battery cell in an oven at a specific temperature (57°C), short-circuit the two poles with a resistor of a specific size (60mΩ), and observe whether there is fire, explosion or gas production. If there is no fire, explosion or gas production, it is considered PASS.

[0137] The above method was used to test the performance of the battery separators of each embodiment and comparative example and the corresponding assembled lithium-ion batteries, and the results are shown in Table 2.

[0138] Table 1

[0139]

[0140] Table 2

[0141]

[0142] According to Table 1 and Table 2, by comparing each embodiment (especially embodiment 1) with comparative example 1, it can be seen that a porous aqueous coating (different from the porous oily coating in embodiment 1) is set on the surface of the heat-resistant ceramic coating away from the base film on the battery separator of comparative example 1, and its adhesion is very poor, and the corresponding lithium-ion battery has serious lithium precipitation at the OH (Over Hang) position of the negative electrode interface during the cycle; while the embodiment adopts a porous oily coating, which has a strong adhesion and can effectively reduce the risk of lithium precipitation due to poor adhesion at the interface OH position. In addition, during the coating preparation process of the battery separator of comparative example 1, due to the poor adhesion of the aqueous slurry, each coating needs to be coated separately, while the porous oily coating is used in the embodiment, and the corresponding oily slurry has strong adhesion and can be coated on both sides at the same time, thereby reducing the number of coatings and reducing production costs.

[0143] Comparing Examples 1, 12, 13, 16, 17 with Comparative Examples 2 and 3, the angle between the extension direction M of the blank unit on the spacing coating layer of the battery separator of Comparative Example 2 and the length direction P of the base film is 0°. After being applied to lithium-ion batteries, the electrolyte cannot diffuse from the head to the middle as quickly as possible during the battery cycle, and the electrolyte bridge appears in the middle, and lithium is seriously precipitated at the interface of the main body; and there are many appearance abnormalities such as streaks or ribs when the battery separator is processed. The angle between the extension direction M of the blank unit on the spacing coating layer of the battery separator of Comparative Example 3 and the length direction P of the base film is 90°, and the corresponding lithium-ion battery has good performance, but the coating scraper and plate roller in the preparation process of the battery separator are seriously worn, and the production cost is high. The extension direction M of the blank unit on the spacing coating layer of the battery separator of Examples 1, 12, 13, 16, and 17 is inclined to the length direction P of the base film, which is conducive to promoting the electrolyte to diffuse from the head to the middle, reducing the risk of lithium deposition in the middle due to electrolyte bridge breaking, and at the same time reducing the appearance abnormalities such as streaks or ribs during the winding process of the separator, and improving the product yield. Specifically, the angle (30°) between the extension direction M of the blank unit and the length direction P of the base film in Example 12 is small, and it is easier for the electrolyte to diffuse from the head to the tail to the middle, and the main body interface is good; the angle (60°) between the extension direction M of the blank unit and the length direction P of the base film in Example 13 is large, and it is relatively difficult for the electrolyte to diffuse from the head to the tail to the middle, and the main body interface is slightly lithium deposited. Therefore, considering the difficulty and wear problem of the plate roller processing, the yield of the separator winding, and the prevention of interface lithium deposition, the angle between the extension direction M of the blank unit on the spacing coating layer of the battery separator and the length direction P of the base film can be controlled at 30° to 60°.

[0144] Comparing Examples 1, 10, 11, 14, and 15, compared with Example 1, the ratio of the width of the oily coating unit to the width of the blank unit (W1 / W2) in the interval coating layer of the battery separator of Example 10 is reduced, the interval between adjacent oily coating units is increased, the adhesion of the coating to the anode (i.e., the negative electrode sheet) is reduced, and slight lithium precipitation occurs at the OH position of the negative electrode sheet interface; compared with Example 1, the ratio of the width of the oily coating unit to the width of the blank unit (W1 / W2) in the interval coating layer of the battery separator of Example 11 is increased, the interval between adjacent oily coating units is reduced, the relative resistance to lithium ion transmission is increased, and slight lithium precipitation occurs at the corner of the battery cell during the cycle process. Therefore, considering the influence of the adhesion between the separator and the electrode sheet and the resistance to lithium ion transmission on lithium precipitation, the ratio of the width of the oily coating unit to the width of the blank unit W1 / W2 in the interval coating layer can be controlled in the range of 0.5 to 3.0.

[0145] Comparing the various embodiments (especially Example 1) and Comparative Example 4, the battery separator of Comparative Example 4 uses a fully coated oily coating layer to replace the gap coating layer of the battery separator of Example 1, which has a large ion transmission resistance, fast capacity decay during the battery cycle, and relatively serious lithium precipitation in the later stage of the main body. The battery separator of Example 1 uses a plurality of oily coating units arranged at intervals to form the gap coating layer, and adjacent oily coating units are arranged at intervals, which can effectively reduce the ion transmission resistance, alleviate the cycle capacity decay and improve the interface lithium precipitation.

[0146] Comparing Examples 1, 8, 9 and Comparative Example 5, the molecular weight of the first organic binder in the porous oily coating of the battery separator of Comparative Example 5 is too small, the crystallinity is high, the material is hard, and the adhesion is very weak, so the OH lithium precipitation at the interface of the negative electrode sheet is serious and the volume expansion is large during the battery cycle. Compared with Comparative Example 5, the molecular weight of the first organic binder in the porous oily coating of the battery separator of Example 8 is increased, the crystallinity is reduced, the adhesion is enhanced, and the lithium precipitation and volume expansion at the interface of the negative electrode sheet during the battery cycle are well improved; the effect of Example 1 is significantly improved compared to Comparative Example 5; the molecular weight of the first organic binder in the porous oily coating of the battery separator of Example 9 is further increased, the crystallinity is further reduced, the adhesion of the material is strong, which affects the diffusion of the electrolyte, and there are slight black spots on the main interface; in addition, if the molecular weight of the first organic binder is too large, the porosity is poor, the air permeability is slightly high, and the lithium ion transmission resistance is large, it may also cause black spots on the main body. In summary, the molecular weight of the first organic binder in the porous oily coating can be controlled within the range of 30W to 100W or 30W to 80W; the first organic binder has a characteristic peak at a diffraction angle between 10° and 40°.

[0147] Comparing Examples 1, 5, 6 with Comparative Examples 6 and 7, the particle size distribution width (D90-D10) / D50 of the polymer particles in the porous oily coating of the battery separator of Comparative Example 6 is relatively large, which is 3.27. The particle size of the polymer particles is very dispersed, and there are many large and small particles. The thickness of the prepared battery separator is uneven and fluctuates greatly. The tabs are easily misaligned when assembling the battery, the battery cell yield is reduced, and the bonding strength is reduced. Lithium deposition is easy to occur at the OH position of the negative electrode interface, and there are many large particles. After the thickness is reduced after hot pressing, the battery cell is at risk of being too thick. In Example 5, the particle size distribution width (D90-D10) / D50 of the polymer particles is reduced to 3.0, the particle size of the polymer particles is slightly dispersed, the amount of large and small particles is relatively reduced, the thickness fluctuation is improved, the adhesion between the porous oily coating and the cathode (i.e., the positive electrode sheet) is significantly enhanced, the cycle test interface is good, and the amount of large particles is relatively reduced. The thickness is reduced after hot pressing, and there is still a slight risk of over-thickness; the particle size distribution width (D90-D10) / D50 of the polymer particles in the battery separator of Example 1 is reduced to 1.5, the battery separator thickness fluctuation is small, the porous oily coating and the positive electrode sheet are strong, the thickness is small after hot pressing, and the product performance is excellent; the particle size distribution width of the polymer particles in Example 6 is further reduced to 1.04, the particle size is relatively concentrated, compared with Example 1, the coating Gap value is slightly smaller, the thickness after hot pressing is slightly thicker, there is a slight risk of overweight, but the cycle test negative electrode sheet interface is good. In contrast, the particle size distribution width (D90-D10) / D50 of the polymer particles in the oily coating of the battery separator in Comparative Example 7 is smaller, and the particle size is more concentrated, but the cost of raw materials is too high. Therefore, considering the production cost and stability, the thickness of the battery cell, and the lithium precipitation at the interface during the cycle, the particle size distribution width (D90-D10) / D50 of the polymer particles in the porous oily coating can be controlled to be 1 to 3.

[0148] Comparing Examples 1, 7 and Comparative Example 8, the flow temperature Tf of the polymer particles in the porous oily coating of the battery separator in Comparative Example 8 is relatively close to the glass transition temperature Tg, and the difference between the two (Tf-Tg) is equal to 5°C. The polymer particles are too soft to play a supporting role and cannot effectively improve the lithium deposition at the corners. The battery corners have serious lithium deposition. In Example 7, the Tf-Tg of the polymer particles is increased to 10°C, and the hardness is enhanced, which can play a certain supporting role. The lithium deposition at the battery corners is improved, and the corners have slight lithium deposition. In Example 1, the Tf-Tg of the polymer particles is increased to 25°C. The polymer particles have strong hardness and can play an effective supporting role. The interface of the battery cycle process is good. As a result, the Tf-Tg of the polymer particles can be controlled above 10°C.

[0149] Comparing Examples 1 and 4 with Comparative Example 9, the glass transition temperature Tg of the heat-resistant glue in the heat-resistant ceramic coating of the battery separator of Comparative Example 9 is too small, the coating has weak heat resistance, the thermal shrinkage rate of the separator is large, the high temperature resistance of the battery is poor, and the high temperature external short circuit test pass rate is 0. The Tg of the heat-resistant glue in Examples 1 and 4 is increased, which can improve the heat resistance of the coating and thus improve the high temperature resistance of the battery. Therefore, the glass transition temperature Tg of the heat-resistant glue in the heat-resistant ceramic coating can be controlled to be greater than or equal to 180°C.

[0150] Comparing Examples 1 to 3 and Comparative Example 10, the particle size distribution width (D90-D10) / D50 of the inorganic ceramic material in the heat-resistant ceramic coating of the battery separator of Comparative Example 10 is too large, the material particle size distribution is too wide, the inorganic ceramic material in the coating is not tightly packed, the thermal shrinkage rate of the separator is large, the high temperature resistance of the battery is poor, and the high temperature external short circuit test pass rate is 0. The particle size distribution width (D90-D10) / D50 of the inorganic ceramic material in Example 2 is reduced to 2.0, the packing density of the inorganic ceramic material in the coating is increased, the thermal shrinkage rate of the separator is reduced, the high temperature resistance of the battery is improved, and the high temperature external short circuit test pass rate is increased. The particle size distribution width (D90-D10) / D50 of the inorganic ceramic material in Example 1 is reduced to 1.33, the inorganic ceramic material in the coating is tightly packed, the thermal shrinkage rate of the separator is small, the heat resistance of the battery is good, and the high temperature external short circuit test pass rate reaches 100%. In Example 3, the particle size distribution width (D90-D10) / D50 of the inorganic ceramic filler is further reduced to 0.67, the material particle size is very concentrated, the coating is compactly stacked, the thermal shrinkage of the diaphragm is small, and the battery has good high temperature resistance, but the inorganic ceramic material cost of this particle size distribution width is high. Therefore, considering the comprehensive production cost and product thermal stability, the particle size distribution width (D90-D10) / D50 of the inorganic ceramic filler can be roughly controlled at 0.5 to 2.

[0151] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A battery separator, characterized in that: include: Basement membrane; A heat-resistant ceramic coating is disposed on a surface of the base film; A porous oily coating is disposed on a surface of the heat-resistant ceramic coating away from the base film; The components of the porous oily coating include polymer particles and a first organic binder; A spacing coating layer is arranged on the surface of the base film away from the heat-resistant ceramic coating; the spacing coating layer includes a plurality of oily coating units arranged at intervals, and blank units are formed between adjacent oily coating units, and the extension direction M of the blank units is inclined to the length direction P of the base film; the components of the oily coating unit include inorganic fillers and a second organic binder.

2. The battery separator according to claim 1, characterized in that: The angle between the extension direction M and the length direction P is 30° to 60°; And / or, the adjacent oily coating unit and the blank unit satisfy: W1 / W2=0.5-3, wherein W1 is the width of the oily coating unit in a direction perpendicular to the extension direction M, and W2 is the width of the blank unit in a direction perpendicular to the extension direction M.

3. The battery separator according to claim 1, characterized in that: In the porous oily coating, the particle size distribution width of the polymer particles satisfies: 0<(D90-D10) / D50≤3; and the difference between the flow temperature Tf and the glass transition temperature Tg of the polymer particles is 10°C to 50°C; And / or, the molecular weight of the first organic binder is 30W-100W, and the first organic binder has a characteristic peak when the diffraction angle 2θ is between 10° and 40°.

4. The battery separator according to claim 3, characterized in that: The polymer particles are selected from at least one of polyamide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, and acrylate copolymers; And / or, the first organic binder is selected from at least one of polyvinylidene fluoride, polyethylene difluoride, polytetrafluoroethylene, hexafluoropropylene, and trifluoroethylene.

5. The battery separator according to claim 1, characterized in that: The components of the heat-resistant ceramic coating include inorganic ceramic material and heat-resistant glue; the particle size distribution width of the inorganic ceramic material satisfies: (D90-D10) / D50=0.5~2, and the glass transition temperature of the heat-resistant glue is greater than or equal to 180°C.

6. The battery separator according to claim 5, characterized in that: The inorganic ceramic material is selected from at least one of silicon dioxide, aluminum oxide, silicon oxide, calcium oxide, magnesium oxide, ZnO, TiO2, boehmite, and ceramic fiber; And / or, the heat-resistant adhesive is selected from at least one of polyacrylic acid and styrene-butadiene rubber.

7. The battery separator according to any one of claims 1 to 6, characterized in that In the spacer coating layer, the molecular weight of the second organic binder is 30W-100W, and the second organic binder has a characteristic peak when the diffraction angle 2θ is between 10° and 40°.

8. The battery separator according to claim 7, characterized in that: The inorganic filler is selected from at least one of silica, alumina, silicon oxide, calcium oxide, magnesium oxide, ZnO, TiO2, boehmite, and ceramic fiber; And / or, the second organic binder is selected from at least one of polyvinylidene fluoride, polyethylene difluoride, polytetrafluoroethylene, hexafluoropropylene, and trifluoroethylene.

9. The method for preparing a battery separator according to any one of claims 1 to 8, characterized in that: The following steps are involved: Disposing a heat-resistant ceramic coating on one surface of the base film; A first oily slurry is prepared by mixing a component including polymer particles and a first organic binder with a first organic solvent; and a second oily slurry is prepared by mixing a component including an inorganic filler and a second organic binder with a second organic solvent; The first oily slurry is coated on the surface of the base film away from the heat-resistant ceramic layer; at the same time, the second oily slurry is coated at intervals on the surface of the base film away from the heat-resistant ceramic coating, and the extension direction of the blank area between adjacent coating areas is inclined to the length direction of the base film, and a battery separator is obtained after drying.

10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a separator sandwiched between the positive electrode sheet and the negative electrode sheet, wherein the separator is the battery separator according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Separator and lithium ion battery

    CN107834007A

  • Functional coating diaphragm and preparation method thereof, lithium ion battery cell, lithium ion battery pack and application of lithium ion battery pack

    CN113451708A

  • Diaphragm, battery and preparation method of diaphragm

    CN115411459A

  • Composite diaphragm as well as preparation method and application thereof

    CN115663399A

  • Composite diaphragm for lithium ion battery and lithium ion battery

    CN117374516A